Webinar Karier: Pilih Prodi yang Tepat untuk Tren Pekerjaan Zaman Now - Rinto Rain Barry; Yohana F. C. Palupi Meilani; Juanna Judith Huliselan; Jacquelinda Sandra Sembel (Universitas Mathla'ul Anwar Banten, 2021)
CAREER WEBINAR: CHOOSE THE RIGHT STUDY PROGRAM FOR TODAY’S JOB TRENDS. The Webinar this time is an activity of the Community Service Team from UPH Business School to Harapan Utama High School, Batam. Based on the results of discussions regarding training needs with related parties, this PKM was carried out with the aim of providing training on choosing majors in higher education for students. With the implementation of this PKM, it is hoped that it can encourage and contribute to the development of knowledge and understanding for students regarding how to choose majors and contemporary work trends that suit their interests and talents and how to prepare themselves to include planning and how to study properly to succeed in the future.